An Overview on Nanotechnology Activities in Iran - S Sarkar; A Beitollahi (Tehran University of Medical Sciences, 2009)
"nDuring the last decade, nanotechnology has gained remarkable attention by international scientific and industrial societies. In this respect, various countries have launched their short and long-term programs to benefit from the huge market expected by utilization and implementation of this technology in their industrial/technological infrastructures. Islamic republic of Iran, also by considering the undeniable impact of this technology on her nation's wealth and economy, initiated her national nanotechnology development plan referred to as "Future Strategy" in 2005. The strategic plan outlines countries major action plans for ten-year period up to 2015 with the target to be amongst the top 15 countries active in this very important area. This paper, while reviewing briefly the objects, targets of the plan will also consider the status and achievements obtained by implementation of this strategic plan. Further, the impact of various developed infrastructures on the success of the program will be also discussed.